Sudden Death from Dilated Cardiomyopathy: ￼Case Report - Sathirareuangchai, Sakda (Siriraj Medical Journal, 2014)
Sudden unexpected death is commonly dealt by a forensic pathologists with sudden cardiac death being a major cause of death in Thai population. Even though dilated cardiomyopathy is the most common type of cardiomyopathy found, it rarely results in sudden death. The author described a case of Thai adult male who was found dead in his bed. The autopsy finding revealed the cause of death to be dilated cardiomyopathy (DCM). Keywords: Sudden death, dilated cardiomyopathy, forensic autopsy Siriraj Med J 2014;66:127-130